Isolation and characterization of bioactive compound from Combretum erythrophyllum leaf extracts - Ledwaba, Imelda Phuti (Vaal University of Technology, 2012)
Combretum erythrophyllum has been used for medicinal purposes and several studies have been carried out to investigate the bioactive compounds present in the leaves of this plant. The World Health Organization reported that 80% of the people living in the developing countries almost exclusively use traditional medicine. Combretum species are used in many human medicines for the treatment of microbial infections and several anti-inflammatory conditions. Members of the Combretaceae family are widely traded in the traditional medicine market in Southern Africa. The family is also used for medicinal purposes in the rest of Africa and Asia for close to 90 medicinal indications. Many of these indications are related to infective agents. Traditional healers have long used plants to prevent or cure infectious conditions. Plants are rich in a wide variety of secondary metabolites, such as tannins, terpenoids, alkaloids and flavonoids, which have been found in vitro to have antimicrobial properties. This review highlights the current status of traditional medicines, its contribution to modern medicine, recent trends in the evaluation of anti-microbial activity with a special emphasis upon some tribal medicine, in vitro and in vivo experimental design for screening and therapeutic efficacy in safety and human clinical trials for commercial outlet. Many of these commercially available compounds are crude preparations administered without performing human clinical trials. The leaves of Combretum erythrophyllum were extracted with acetone to obtain the crude extract. Liquid-liquid fractionation was performed on the crude using different solvents of different polarity. The crude and obtained fractions were investigated for antimicrobial activity. The crude and fractions were tested against certain bacterial and fungal microorganisms. The assay methods used included the microtitre dilution method for determining the minimum inhibitory concentration and bioautographic methods used to detect the inhibition of bacterial and fungal growth by active compounds separated from the crude and fractions. The antioxidant activity was performed using TLC-DPPH, DPPH, ABTS and hydroxyl radical scavenging. The toxicity of crude extract and fractions was determined using MTT assay. Isolation of compounds was performed using column chromatography. Structural elucidation was done using NMR and MS spectrometry. In microtitre dilution assay acetone fraction inhibited the growth of S. aureus, E. faecalis, P. aeruginosa with the lowest MIC value of 0.02, 0.32, 0.16 μg/ml and ethyl acetate fraction inhibited the growth of E. coli with the lowest MIC value of 0.16 μg/ml. All fractions were active against C. neoformans with the MIC value of 0.02 μg/ml. Dichloromethane was the least active against C. albicans with the MIC value of 0.16 μg/ml while the rest had the MIC value of 0.08 μg/ml. Dichloromethane was found to be active against A. fumigatus with the lowest MIC value of 0.16 μg/ml. Bioautography showed the presence of various inhibitory chemical compounds. Ethyl acetate and hexane fraction had a very good separation and showed various zones of inhibition on exposure to E. faecalis, E. coli, S. aureus and P. aeruginosa with the Rf values ranging from 0-0.98. Crude and fractions showed slight zones of inhibition against C. neoformans, C. albicans and A. fumigatus with the Rf values ranging from 0-0.76. TLC-DPPH assay displayed that ethyl acetate and water fraction had the highest antioxidant activity in CEF. Ethyl acetate fraction had a strong antioxidant activity in DPPH assay with the EC50 of 0.04272 μg/ml, water fraction showed a good antioxidant activity with the EC50 of 0.01825 μg/ml in ABTS assay and in the hydroxyl radical scavenging the crude extract scavenged 77.62 ± 1.41% at the highest concentration of 0.250 mg/ml and 47.21 ± 3.20% at the lowest concentration of 0.003 mg/ml. The toxicity level of the crude extract and fractions were found to be between 34 and 223 mg/ml which were all below doxorubicin (LC50 = 7.1855 μg/ml) which was used as the positive control. Column chromatography was used in a bio-guided assay fractionation and led to isolation of one compound. The antimicrobial activity was determined against pathogenic bacteria. The isolated compound had a good activity against Pa and Sa with the lowest MIC value of 0.32 μg/ml. Nuclear magnetic resonance spectroscopy (NMR) and mass spectroscopy were used for the identification of isolated compounds. One compound was isolated and identified as Friedelin. The results obtained confirm that the leaves of Combretum erythrophyllum have a good antimicrobial activity and strong antioxidant activity.
M. Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Combretum erythrophyllum; Traditional medicine.; Dissertations, Academic -- South Africa.; Anti-inflammatory agents.; Medicinal plants -- South Africa.